What Open Source Software Research Can Teach Us About Public Blockchain(s)?—Lessons for Practitioners and Future Research - Lindman, Juho (Frontiers in Human Dynamics, 2021)
Peer-to-peer governance of blockchain technology reemerges a number of interesting practical and theoretical questions. This article aims to bridge current research on blockchain technology to earlier research on open source software (OSS) and to suggest a number of concepts from OSS research that are useful in discussing governance of blockchain systems. Thus, the purpose of this article is to provide a theoretically oriented review of some of the earlier concepts and discuss their applicability in a novel context. Bridging these extending literatures and concepts accelerates theoretical development in the area of governance of technology, opening fertile avenues for future research and offering a variety of insights to both practitioners.